Optimalisasi Manajemen Kinerja dan Teknologi Digital dalam Meningkatkan Kualitas Pelayanan Publik pada Disdukcapil Kota Surabaya - Muhammad Fu’ad Abdullah; Rukin Rukin; Ady Setiawan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze strategies for improving service quality at the Population and Civil Registration Office (Disdukcapil) of Surabaya City through performance management of apparatus, optimization of digital technology utilization, and integration of good governance principles. Disdukcapil faces complex challenges due to high population mobility and increasing public demands for fast, transparent, and accountable services. Using a qualitative approach with observations and in-depth interviews with apparatus and service users, the study finds that successful public service delivery depends not only on system modernization but also on the capability of human resources to operate the system professionally and with integrity. Implementation of performance appraisal based on Employee Performance Targets (SKP), competency evaluations, and a fair reward and punishment system are crucial foundations to encourage productivity and an adaptive work culture. Information technology acts as an accelerator for service efficiency but is only effective if supported by adequate digital literacy among the public. Therefore, strategies to enhance service quality must combine strengthening internal bureaucratic capacity with empowering the community as active partners. The study concludes that the success of local public service reform relies on harmonizing policy instruments, digital infrastructure, and good governance values. Bureaucratic transformation oriented toward public satisfaction must be built through accountable, responsive, and inclusive systems to deliver excellent, fair, and sustainable services. The findings provide important foundations for formulating equitable and performance-based public service policies.